Evaluation of obstructive sleep apnea in obese patients scheduled for bariactric surgery - Lopes Neto,José Maurício (2013)
PURPOSE: To evaluate the frequency of obstructive sleep apnea (OSA) in obese patients scheduled for bariatric surgery and their identification for risk of OSA by Berlin Questionnaire (BQ) and excessive daytime sleepiness by Epworth Sleepiness Scale (ESS). METHODS: Fifty nine patients were evaluated by BQ and ESS. Out of these individuals, 35 performed a full-night sleep study using a type 3 portable monitoring (PM). The questionnaire results were compared for gender and BMI. The presence and severity of OSA was correlated with gender and both questionnaires. RESULTS: 94.75% of the respondents presented high risk for OSA by BQ and 59.65% presented positivity by ESS. Taking into account the AHI> 5 per hour for OSA diagnosis, all of them presented OSA, average AHI of 45.31±26.3 per hour and 68.6% have severe OSA (AHI>30). The male patients had a higher AHI (p<0.05). There was a positive correlation between the positivity in both questionnaires as well as the severity of OSA measured by AHI (p<0.05). CONCLUSION: The frequency and severe obstructive sleep apnea in the studied group is high. The Berlin Questionnaire and Epworth Sleepiness Scale had a positive correlation with the diagnosis of OSA in the group studied.